Anti-diabetic, anti-cholinesterase, and antioxidant potential, chemical composition and sensory evaluation of novel sea buckthorn-based smoothies. (15th February 2021) - Tkacz, Karolina; Wojdyło, Aneta; Turkiewicz, Igor Piotr; Nowicka, Paulina
Highlights: Eighteen new sea buckthorn-based smoothies with fruits and vegetables were composed. Fruits and vegetables improved sugar:acid ratio and sensory acceptance of products. Smoothies were a source of flavonols, phenolic acids and procyanidins (UPLC-PDA-FL) The ability to inhibit butylcholinesterase was higher than for acetylcholinesterase. Smoothies were good inhibitors of α -amylase, α -glucosidase and pancreatic lipase. Abstract: Sea buckthorn berries fit into the strategy of seeking natural factors in the non-communicable diseases prevention, but their sensory qualities are a challenge for consumers and food industry. The study aimed to evaluate anti-cholinesterase (anti-acetylcholinesterase and -butylcholinesterase), anti-diabetic (anti- α -amylase, - α -glucosidase, -pancreatic lipase) and antioxidant potential (FRAP, ORAC), phenolic compounds (UPLC-PDA-FL), basic chemical composition, and sensory quality of sea buckthorn-based smoothies. Eighteen novel products containing sea buckthorn (25–50%) with other fruits and vegetables were analyzed. Sea buckthorn enriched the smoothies in flavonols (25.46–95.13 mg/100 g), and fruits and vegetables provided phenolic acids and procyanidins. The anti-BuChE effect was higher than anti-AChE, while products with apricot, orange, grape and parsley root were strong inhibitors of carbohydrates digesting enzymes. Lipase inhibition by all smoothies was over 50%. Products with 75% fruits or 50% vegetables were the most sensory attractive. The results will be valuable in designing innovative food with rarely used berries.